How Is Religiousness Associated With Adolescent Risk‐Taking? The Roles of Emotion Regulation and Executive Function. (17th June 2019) - Holmes, Christopher; Brieant, Alexis; King‐Casas, Brooks; Kim‐Spoon, Jungmeen
Abstract : Existing literature has demonstrated an association between higher adolescent religiousness and lower risk‐taking via higher self‐regulation. This study sought to elucidate the roles of emotion regulation and executive function as parallel mediators in the link between religiousness and risk‐taking in a sample of 167 adolescents (mean age = 14.13 years, 52% male, 82% White at Time 1). Longitudinal results across three waves utilizing structural equation modeling indicated higher religiousness was associated with higher emotion regulation, whereas religiousness was not associated with executive function. Subsequently, higher emotion regulation and executive function were associated with lower risk‐taking. Emotion regulation mediated the association between religiousness and risk‐taking. The findings highlight religiousness as a contextual protective factor for adolescents.